Quantitative assessment of phagocytic activity of hemocytes in the prawn, Penaeus merguiensis, by flow cytometric analysis - Lee, Y.K. (2012)
10.1002/1097-0320(20010101)43:1<82::AID-CYTO1021>3.0.CO;2-L